2015
DOI: 10.1155/2015/821279
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and Its Potential Use as a Scaffold for Tissue Engineering in Regenerative Medicine

Abstract: Tissue engineering is an important therapeutic strategy to be used in regenerative medicine in the present and in the future. Functional biomaterials research is focused on the development and improvement of scaffolding, which can be used to repair or regenerate an organ or tissue. Scaffolds are one of the crucial factors for tissue engineering. Scaffolds consisting of natural polymers have recently been developed more quickly and have gained more popularity. These include chitosan, a copolymer derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
353
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 494 publications
(374 citation statements)
references
References 120 publications
2
353
0
19
Order By: Relevance
“…This allows them to have better performance in service. Natural polymer can be classified as proteins such as silk, collagen, fibrinogen, elastin and myosin, polysaccharides such as cellulose, amylose, dextran, chitin, chitosan and glycosaminoglycan, or polynucleotides, deoxyribonucleic acid, DNA, and ribonucleic acid, RNA [8].…”
Section: Introductionmentioning
confidence: 99%
“…This allows them to have better performance in service. Natural polymer can be classified as proteins such as silk, collagen, fibrinogen, elastin and myosin, polysaccharides such as cellulose, amylose, dextran, chitin, chitosan and glycosaminoglycan, or polynucleotides, deoxyribonucleic acid, DNA, and ribonucleic acid, RNA [8].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was demonstrated that glutaraldehyde crosslinking of collagen scaffold have increased the vascularization in a murine subcutaneous implantation model [18]. Natural scaffolds have greater biological interaction with the cells due to their bioactive properties which allow them to have better performance in the biological system [19] Collagen: Collagen represents the principal component of ECM; it's a natural protein with a triple-helix structure, which can form a reversible gel. This protein presents excellent tissue compatibility, facile biodegradation and its degradation products are absorbed facilely without inflammation.…”
Section: Biomaterials In Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Like the native cartilage, this polymer contains glycosaminoglycan (GAG) and hyaluronic acid, presents properties such as biocompatibility, biodegradability and non-toxicity and in the last years it was very used in the cartilage tissue engineering field. The main disadvantage of this polymer refers to the lack of gelling properties, leading to the possibility that it will flow out of the joint when applied, forming cartilage-like tissue ectopically [19,20,28].…”
Section: Biomaterials In Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Chitosan and chitosan hydrogels are approved by the US Food and Drug Administration for use in tissue engineering, and drug delivery and are currently used in the repair of skin, nerve, cartilage, and bone [8,9]. Hydrogels made from chitosan are liquid at room temperature but undergo gelation and form a matrix at body temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these gels can be directly injected into the heart during cardiac surgery or injected by catheter into the LV endocardium at cardiac catheterization. Chitosan gels are biocompatible, non-toxic, bacteriostatic, and are porous [8,9]. Therefore chitosan gels permit the diffusion of cells and nutrients to the myocardium.…”
Section: Introductionmentioning
confidence: 99%